Assessment of ultrafine particles in Portuguese preschools: levels and exposure doses - Fonseca, J. (2015)
The aim of this work was to assess ultrafine particles (UFP) number concentrations in different microenvironments of Portuguese preschools and to estimate the respective exposure doses of UFP for 3–5-year-old children (in comparison with adults). UFP were sampled both indoors and outdoors in two urban (US1, US2) and one rural (RS1) preschool located in north of Portugal for 31 days. Total levels of indoor UFP were significantly higher at the urban preschools (mean of 1.82x104 and 1.32x104 particles/cm3 at US1 an US2, respectively) than at the rural one (1.15x104 particles/cm3). Canteens were the indoor microenvironment with the highest UFP (mean of 5.17x104, 3.28x104, and 4.09x104 particles/cm3 at US1, US2, and RS1), whereas the lowest concentrations were observed in classrooms (9.31x103, 11.3x103, and 7.14x103 particles/cm3 at US1, US2, and RS1). Mean indoor/outdoor ratios (I/O) of UFP at three preschools were lower than 1 (0.54–0.93), indicating that outdoor emissions significantly contributed to UFP indoors. Significant correlations were obtained between temperature, wind speed, relative humidity, solar radiation, and ambient UFP number concentrations. The estimated exposure doses were higher in children attending urban preschools; 3–5-year-old children were exposed to 4–6 times higher UFP doses than adults with similar daily schedules.